Aptitud maternal en tres genotipos de cuyes mejorados provenientes de un proceso de reconversión genética - Aizana-Yupari, Juan (2025)
Attributes related to maternal ability in three improved guinea pig genotypes resulting from a genetic reconversion process were evaluated. The guinea pigs belonged to the Yauris Agricultural Experimental Station (Junín, Peru). Litter size at birth (LSB) and weaning (LSW), litter weight at weaning (LW), pup weight at birth (LBW) and at weaning (LSW), and pup survival rate (PSR) were evaluated. Genotypes were differentiated by their coat colour: red-R (n=68), white-R (24), and bay-R (19). Dams were monitored for five months in their respective breeding pens under a mating system. The bay-R genotype had the highest weight at birth (162.2 ± 28.5 g) and weaned (325.4 ± 40.1 g) offspring, but a lower PSR (79.1%). The red-R and white-R genotypes stood out for their higher LSB (3.76 ± 1.05 and 3.45 ± 0.9), LSW (3.13 ± 0.88 and 3.20 ± 0.91) and LW (839.0 ± 247.0 and 826.5 ± 215.9 g), which together with the white-R genotype showed the highest PSR (92.8%). In conclusion, the bay-R genotype stands out for the precocity of its offspring, although with lower survival, while the red-R and white-R genotypes stand out for their greater prolificacy and survival rates, which makes them better maternal producers.